Cultural Influence of Local Food Heritage on Sustainable Development - Gladys Ogochukwu Chukwurah; Francis Ogochukwu Okeke; Matthew Ogorchukwu Isimah; Evidence Chinedu Enoguanbhor; Foluso Charles Awe; Rosemary Chidimma Nnaemeka-Okeke; Shuang Guo; Ifeanyichukwu Valentine Nwafor; Chioma Angela Okeke (World)
This article explores relations between cultural heritage and cultural values for sustainable development in the Enugu region. It discusses the potential to advance a cultural approach to sustainable development of regions by examining the cultural food heritage and relating it to cultural values. Based on empirical research, the article employed a mixed-methods approach to examine the relationship between the identified major local food heritage and cultural values for sustainable regional planning and development. The study examined primary data from 380 community elders, traders, and relevant institutions—including the Ministry of Arts and Culture and the Ministry of Agriculture—through interviews, participant observation, and questionnaires. Data were analyzed using SPSS and Pearson product–moment correlation. Findings identified eight local food heritages and six cultural values. The findings suggest that promoting and preserving local food heritage can be crucial in fostering sustainable cultural values and contributing to sustainable regional development. The local food had a statistically significant influence on cultural values. The Pearson correlation result (p-value = 0.000) shows a strong correlation between the local food heritage and cultural values for sustainable regional planning and development. However, the study also identified several challenges threatening the sustainability of local food heritage in the region, including high costs, small-scale farming, insecurity, climate change, and poor transportation. The study recommends the development and implementation of comprehensive policies and programs that prioritize the preservation and promotion of local food heritage while addressing the identified challenges.